The passengers on the Hankyu line - Arikawa, Hiro; Powell, Allison Markin (London : Doubleday, 2025)
"Welcome aboard the Hankyu train! Come along on a heartwarming, funny, and a perfectly cozy voyage with the charming and relatable passengers-including one dashing dachsund-whose lives intersect and affect each other on one of Japan's most romantic railway lines from the international bestselling author Hiro Arikawa. Between the two beautiful Japanese towns of Takarazuka and Nishinomiya, in a stunning mountainous area of Japan, rattles the Hankyu train. Passengers step on and off, lost in thought, contemplating the tiny knots of their existence. On the outward journey we are introduced to the emotional dilemmas of five characters, and on the return journey six months later, we watch them resolve. A young man meets the young woman who always happens to borrow a library book just before he can take it out himself; a woman in a white bridal dress boards looking inexplicably sad; a university student leaves his hometown for the first time; a girl prepares to leave her abusive boyfriend; and an old lady discusses adopting a dog with her granddaughter. These fully developed stories crisscross each other like the railway lines in the book. As ever with Arikawa's writing, the characters are vivid and delightful, their predicaments touching on universal human desires and emotions that feel utterly familiar. Her warmth spills over, alongside a fierce wit, a bit of fun railway geekery, and plenty of delicious detail about the beauties and traditions of the Japan we travel through with these unforgettable passengers"-- $c Provided by publisher.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Man-woman relationships -- Fiction; Rail passengers -- Japan -- Fiction; Man-woman relationships -- Japan -- Fiction